2016
DOI: 10.1111/adb.12460
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of opiate‐mediated behaviors by the selective TRPV1 antagonist SB366791

Abstract: Transient receptor potential vanilloid type 1 (TRPV1), the archetypal member of the vanilloid TRP family, was initially identified as the receptor for capsaicin, the pungent ingredient in hot chili peppers. We previously demonstrated that TRPV1 in the dorsal striatum significantly contributes to morphine reward by using the conditioned place preference paradigm in mice; however, it is unknown whether TRPV1 has the same effect in other reward models. In this study, we investigated the role of TRPV1 in morphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Several recent studies have shown that TRPV1 channels play a crucial role in drug addiction disorders (Ma et al, 2017; Tian et al, 2018) highlighting the need to further explore the role of TRPV1R in the modulation of the reward system. VTA DA neurons, together with their afferents to the NAc and prefrontal cortex, constitute a crucial neuronal circuit in drug addiction and drug‐seeking behaviour (Kauer & Malenka, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have shown that TRPV1 channels play a crucial role in drug addiction disorders (Ma et al, 2017; Tian et al, 2018) highlighting the need to further explore the role of TRPV1R in the modulation of the reward system. VTA DA neurons, together with their afferents to the NAc and prefrontal cortex, constitute a crucial neuronal circuit in drug addiction and drug‐seeking behaviour (Kauer & Malenka, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, our results show a modulatory role of TRPV1 on the effects of chronic nicotine administration in mice behaviour, though not at the cellular level. This discrepancy may suggest that TRPV1 receptor control on nicotine‐induced locomotor sensitization does not depend on VTA TRPV1R but on TRPV1R expressed in more downstream structures of the mesolimbic dopaminergic system, such as NAc (Ma et al, 2017; You et al, 2019). Future experiments should be conducted to explore this prospect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same result is found in the NAc; for example, TRPV1 knock-out mice do not exhibit morphine reward responses, and intraperitoneal and intra-NAc injections of SB366791 reduce morphine-induced CPP in wild-type mice [ 56 ]. Furthermore, TRPV1 has a consistent effect in the morphine self-administration paradigm [ 34 ], which may relevantly model drug-taking behavior in a natural environment and be regarded as a gold-standard indicator of addiction [ 59 ]. Blocking the TRPV1 receptor with SB366791 significantly reduces morphine self-administration in rats on a fixed-ratio 1 schedule or a progressive ratio schedule of reinforcement, i.e., suppresses the motivational properties of morphine and its reinstatement or relapse [ 34 ].…”
Section: Addictionmentioning
confidence: 99%
“…Intrathecal or intraperitoneal pretreatment with the TRPV1 antagonist SB366791 or capsazepine reduces morphine tolerance and the associated thermal hyperalgesia [ 29 ]. In addition, blocking TRPV1 receptors in the reward system, particularly expressed in the striatum and nucleus accumbens (NAc), attenuates opiate-mediated reward behaviors, including conditioned place preference (CPP) and morphine self-administration in rodents [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%